Éclairage théorique sur le sens et la signification de l’innovation en éducation dans les systèmes de formation : diachronie et synchronie - Françoise Cros (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
enSince the school was created, educators and teachers have tried to adjust their practices to new and intuitive ideas (sometimes supported by contextualized research results) that be “good” or even best learning situations for young people.Multiple innovative attempts have thus been launched over the centuries that the history education in France clearly shows (Prost, 1992). So how is it that innovation is currently at the core of the main concerns of the evolution of our training systems if it is consubstantial with educational systems?The question of innovation in education from its name “innovation” emerged in Western countries in the 1960s in close connection with technology innovation of modern companies. Contemporary capitalism with its adjuvants has not doubt facilitated its notoriety (Schumpeter, 1965). But we can designate under the same word an innovation such as the placing on the market of a new car and a new pedagogy! Can we substantialize a market and an educational relationship?Do we not confuse the introduction of a new object (such as ICT) in educational uses and its use in a singular process that is learning? In other words, innovation in education cannot simply be assimilated to a new technical object. Furthermore, the conceptions of innovation have evolved in an increasing complexity relationship to objects, to time and to Others. This contribution attempts to clarify the question.innovation, numérique, éducation, enseignement supérieur, société